Sports medicine applied to baseball - Ante Vidal, G.; Beltrami, G.; Bokor, D.; Boyd, W.; Masujima, A.; Varriale, L. (2001)
List of contents: Sport Training Medical Control (Dr. Gilberto Ante Vidal) Public Health Issues in Baseball (Dr. William Boyd) Nutrition in Baseball (Dr. Gianfranco Beltrami) Children and Baseball (Dr. Desmond Bokor) Infectious Diseases in Baseball (Dr. Gianfranco Beltrami) Drugs: Use and Abuse (Dr. William Boyd) Doping and Health Risks (William Boyd) Injury Prevention in Baseball (Dr. Gilberto Ante Vidal) Injuries in Baseball Players: Hand - Elbow - Shoulder (Dr. Leo Varriale) Injuries in Baseball Players: Back - Thigh - Knee - Lower Leg - Ankle (Dr. Atsushi Masujima)